RANCANG BANGUN MESIN PEMURNIAN VIRGIN COCONUT OIL (VCO) DENGAN METODE SENTRIFUGAL BERBASIS INTERNET OF THGINGS (IoT) - Pankrasianus Josri Sudirman; Ayu Aprilyana Kusuma Dewi; I Wayan Dika (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
Virgin Coconut Oil (VCO) is a virgin coconut oil produced from the extraction process of fresh coconut meat without the use of chemicals or high temperatures. VCO has high economic value with various health benefits. The process of making VCO involves a centrifugal machine to separate the oil from coconut milk. However, the control of the VCO Purification machine still relies on manual intervention by the operator, which can lead to human error and affect production efficiency. In order to improve efficiency and reduce the risk of human error, Internet of Things (IoT) and Mobile Application technologies can be applied in the control of VCO Purification machines. The programming language used is PHP because it can be accessed on various platforms, especially Mobile. The sensor used is an IR (Infrared) speed sensor for measuring rotational speed. The Mobile Application can be a convenient interface for operators to control and record the operation history of the VCO purification machine. This research has succeeded in developing an IoT and Mobile Application-based control system that is effective in controlling VCO purification machines, increasing production efficiency, and reducing the risk of human error.